2017
DOI: 10.1136/bmjopen-2016-012252
|View full text |Cite
|
Sign up to set email alerts
|

Relative bioavailability of single doses of prolonged-release tacrolimus administered as a suspension, orally or via a nasogastric tube, compared with intact capsules: a phase 1 study in healthy participants

Abstract: ObjectiveTacrolimus, an immunosuppressant widely used in solid organ transplantation, is available as a prolonged-release capsule for once-daily oral administration. In the immediate postsurgical period, if patients cannot take intact capsules orally, tacrolimus therapy is often initiated as a suspension of the capsule contents, delivered orally or via a nasogastric tube. This study evaluated the relative bioavailability of prolonged-release tacrolimus suspension versus intact capsules in healthy participants.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 15 publications
0
14
2
Order By: Relevance
“…A previous Phase I study [14] compared systemic exposure of tacrolimus after administration of the contents of prolonged-release tacrolimus capsules via intact capsules, oral suspension, or nasogastric suspension in healthy volunteers. The data indicated that administration of prolonged-release tacrolimus suspension, orally or via nasogastric tube, resulted in a faster absorption profile (shorter T max and higher C max ) compared with intact capsules.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A previous Phase I study [14] compared systemic exposure of tacrolimus after administration of the contents of prolonged-release tacrolimus capsules via intact capsules, oral suspension, or nasogastric suspension in healthy volunteers. The data indicated that administration of prolonged-release tacrolimus suspension, orally or via nasogastric tube, resulted in a faster absorption profile (shorter T max and higher C max ) compared with intact capsules.…”
Section: Discussionmentioning
confidence: 99%
“…The data indicated that administration of prolonged-release tacrolimus suspension, orally or via nasogastric tube, resulted in a faster absorption profile (shorter T max and higher C max ) compared with intact capsules. Mean exposure (estimated using AUC) was approximately 17% lower for nasogastric tube administration compared with intact capsules [14]. The authors speculated that incomplete tacrolimus absorption profiles were recorded for the participants who reached C max at the first blood-sampling time point, leading to an underestimation of the overall systemic exposure to tacrolimus.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations